Pengaruh Kepadatan Awal Inokulum terhadap Kualitas Kultur Chaetoceros gracilis (Schütt) pada Sistem Batch - Gede Suantika; Pingkan Adityawati; Dea Indriani Astuti; Yusup Sofyan (Institut Teknologi Bandung, 2009)
Chaetoceros gracilis (Schütt) is a common live food used in white shrimp Litopenaeus vanamei larviculture that is commonly produced by using batch culture system. The aim of this study was to evaluate the effect of different initial densities inoculums to obtain the optimum quality of C. gracilis culture in batch culture system. Based on the result from step 1, the highest cell density of 9,85x106 ± 5,00x105 cells/mL was obtained in the culture with inoculum initial density of 1,0x105 cells/mL. At step 2, the highest cell density of 9,87 x 106 ± 2,00 x 105 cells/mL was obtained in the culture with inoculum initial density of 1,0x105 cells/mL and it was significantly (p